Aktivitas Antidiabetes Ekstrak Etanol Daun Jambu Biji (Psidium guajava L.) terhadap Analisis Berat Badan Tikus yang Diinjeksi Streptozotocin - Rahayu, Nila Rusdi; Badriyah, Lailatul; Mutripah, Siti (Sultan Agung Islamic University of Semarang, 2025)
Background: Diabetes mellitus (DM) refers to a medical condition impacting the body's metabolism of lipids, carbohydrates, and proteins, stemming from issues with pancreatic endocrine hormones like insulin and glucagon. This study aimed to test the ability of ethanol extract from guava leaves to reduce blood glucose levels in rats injected with streptozotocin (STZ), and to evaluate the effect of the ethanol extract on food consumption. Methods: This antidiabetic test was conducted on rats injected with streptozotocin (STZ) by measuring the increase in blood glucose levels and body weight in rats experiencing hyperglycemia. The experimental animals were split into four categories, and each category had six rats. The rats in Group I received regular sustenance, the rats in Group II were given CMC Na solution, the rats in Group III received 5mg/kg BW of gliclazide, and the rats in Group IV were administered 300mg of guava leaf extract. A 40mg/kg BW streptozotocin injection was given intraperitoneally on day 0. Blood glucose levels were assessed on days 7, 14, and 21. Data analysis used oneway Anova and followed by The Kolmogorov-Smirnov test was used to assess the normality of the blood glucose and body weight data. Results: The results of study showed On day 21, a significant difference was seen between the STZ-injected group with EEDJ extract treatment 300mg/kg bb and the STZ-injected group intraperitoneally and given Gliclazide 5 mg/kg BW (p<0.05), but there was no significant difference. Conclusion: Administration of EEDJ extract and gliclazide has shown a significant decrease in blood glucose levels and greatly prevent weight loss.